Augmented cystine–glutamate exchange by pituitary adenylate cyclase‐activating polypeptide signaling via the VPAC1 receptor. Issue 12 (6th August 2014) - Resch, Jon M.; Albano, Rebecca; Liu, Xiaoqian; Hjelmhaug, Julie; Lobner, Doug; Baker, David A.; Choi, Sujean
ABSTRACT In the central nervous system, cystine import in exchange for glutamate through system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcn5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> is critical for the production of the antioxidant glutathione by astrocytes, as well as the maintenance of extracellular glutamate. Therefore, regulation of system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcrt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> activity affects multiple aspects of cellular physiology and may contribute to disease states. Pituitary adenylate cyclase‐activating polypeptide (PACAP) is a neuronally derived peptide that has already been demonstrated to modulate multiple aspects of glutamate signaling suggesting PACAP may also target activity of cystine–glutamate exchange via system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcq8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives>. In this study, 24‐h treatment of primary cortical cultures containing neurons and glia with PACAP concentration‐dependently increased system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcsc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> function as measured by radiolabeled cystine uptake. Furthermore, the increase in cystine uptake was completely abolished by the system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvctx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> inhibitor, (S)‐4‐carboxyphenylglycine (CPG), attributing increases in cystine uptake specifically to system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcvg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> activity. Time course and quantitative PCR results indicate that PACAP signaling may increase cystine–glutamate exchange by increasing expression of xCT, the catalytic subunit of system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcw1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives>. Furthermore, the potentiation of system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvcxk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> activity by PACAP occurs via a PKA‐dependent pathway that is not mediated by the PAC1R, but rather the shared vasoactive intestinal polypeptide receptor VPAC1R. Finally, assessment of neuronal, astrocytic, and microglial‐enriched cultures demonstrated that only astrocyte‐enriched cultures exhibit enhanced cystine uptake following both PACAP and VIP treatment. These data introduce a novel mechanism by which both PACAP and VIP regulate system <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fddvb8k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />xc−</alternatives> activity. Synapse 68:604–612, 2014. © 2014 Wiley Periodicals, Inc.